Implementasi Model Pembelajaran Discovery Learning Dalam Meningkatkan Keterampilan Sosial Pada Siswa Kelas V SD Kartika XIII-1 Ambon: Indonesia - Lapandewa, Kastina; Ritiauw, Samuel Patra; Mahananingtyas, Elsinora (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the implementation of the discovery learning model in improving students' social skills. In this study using a quantitative descriptive with one group pre-test and post-test designs, while the data collection technique used a questionnaire. Furthermore, the data obtained was analyzed using the N-Gain Formula to determine the improvement of social skills through questionnaires. The results showed that there were significant variations in the level of mastery of social skills between indicators and between assessment categories (SS, S, TS, STS) with the highest average percentage in the Agree (S) category with 15.2%, followed by Strongly Agree (SS) by 17.7%, then Strongly Disagree (STS) by 8%, and the lowest was Disagree (TS) by 6.2%.